Contracting Students for the Reduction of Foreign Language Classroom Anxiety: An Approach Nurturing Positive Mindsets and Behaviors - Jin, Yinxing; Zhang, Lawrence Jun; MacIntyre, Peter D. (Frontiers in Psychology, 2020)
The quasi-experimental study as reported in this paper investigated whether contracting students’ speaking in the foreign language (FL) classroom could effectively mitigate their FL classroom anxiety. It also explored the working mechanisms of this approach to the reduction of classroom anxiety and examined the attitudes FL students had towards it. To these ends, 42 Chinese-as-the-first language university students learning English as a foreign language (EFL) were recruited and placed into the experimental (n = 20) and comparison groups (n = 22). Both groups were tested for anxiety before and after completing a 1-week contract and a non-contracting treatment respectively. The experimental group participants’ diaries were also collected and their attitudes towards the intervention were elicited. Results showed that the experimental group’s level of anxiety decreased significantly more as compared with that of the comparison group’s, suggesting the better efficacy of contracting speaking in FL anxiety reduction. Diary analyses also suggested that contracting speaking could increase learners’ FL learning engagement, enhance their self-efficacy, facilitate their self-reflection of weaknesses and strengths as an FL learner, cultivate their character strengths and positive emotions, and diminish their fear, nervousness, and worries in class. Furthermore, the experimental group participants generally did not feel uncomfortable with the intervention. These findings were discussed in relation to classroom pedagogy for more effective delivery of FL education.